2020
DOI: 10.1371/journal.pone.0225917
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional programming improves dietary plant protein utilization in zebrafish Danio rerio

Abstract: Nutritional Programming (NP) has been shown to counteract the negative effects of dietary plant protein (PP) by introducing PP at an early age towards enhancement of PP utilization during later life stages. This study explored the effect of NP and its induction time on growth, expression of appetite-stimulating hormones, and any morphological changes in the gut possibly responsible for improved dietary PP utilization. At 3 days post-hatch (dph) zebrafish were distributed into 12 (3 L) tanks, 100 larvae per tan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
6
25
0
Order By: Relevance
“…Considering the orexigenic signals analyzed in the present study, all the groups fed BSF-based diets showed a significant ghrl , npy and cnr1 downregulation compared to F1Hi0. These results are in line with the biometric ones and with a previous study in which nutritionally programmed zebrafish were found to be in a satiated state compared to the control groups [ 80 ]. Conversely, the higher orexigenic signals gene expression found in all F0 zebrafish larvae fed on BSF-based diets was related to a compensatory mechanism that increased food intake with a consequent faster growth rate, possibly in relation to dietary deficiency of important nutrients, like DHA [ 8 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering the orexigenic signals analyzed in the present study, all the groups fed BSF-based diets showed a significant ghrl , npy and cnr1 downregulation compared to F1Hi0. These results are in line with the biometric ones and with a previous study in which nutritionally programmed zebrafish were found to be in a satiated state compared to the control groups [ 80 ]. Conversely, the higher orexigenic signals gene expression found in all F0 zebrafish larvae fed on BSF-based diets was related to a compensatory mechanism that increased food intake with a consequent faster growth rate, possibly in relation to dietary deficiency of important nutrients, like DHA [ 8 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nutritional programming may make it possible to obtain fish better adapted to use specific dietary ingredients, also by acting on the gastrointestinal tract which, in fish, is able to adapt to rapid shifts in environmental conditions, including diet [ 80 , 81 , 82 ]. In the present study, no specific inflammatory events and no differences in histopathological indexes were detected through the histological analyses on F1 zebrafish larvae intestine from any of the dietary treatments.…”
Section: Discussionmentioning
confidence: 99%
“…6 NP with PP shows great promise to increase utilization of lower-quality PP sources. 1,5,[7][8][9] Studies have challenged rainbow trout (Oncorhynchus mykiss) with vegetable oil-based diets and reported that the fish later presented higher feed intake, growth, and feed utilization compared to nonprogrammed individuals. 1,10 Previous research has also provided insight that early NP of rainbow trout alevins might lead to similar alpha diversity measures of gut microbes between programmed versus nonprogrammed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, NP with dietary carbohydrates from plant products initially improved growth performance in European sea bass (Dicentrarchus labrax) larvae; however, programming effects faded over time and no signifcant difference in growth was observed between programmed and nonprogrammed juveniles [31]. Interestingly, a similar study performed in our laboratory under the same conditions did find that NP improved growth performance of fish fed a SBM diet [32]. One possible explanation for the lack of programming influence in the present study could be species-specific differences.…”
Section: Growth Performancementioning
confidence: 59%